Studies on Genetic Variability, Heritability, Correlation and Path Analysis in Chrysanthemum (Dendranthema grandiflora Tzvelev) - Bennurmath, Parvathi; Kumar, Rajiv; Nair, Sujatha A.; R, Venugopalan; M. V, Dhananjaya; R. H., Laxman (International Journal of Bio-resource and Stress Management, 2022)
The studies were conducted in the Division of Flower and Medicinal Crops, ICAR-Indian Institute of Horticultural Research, Bengaluru to evaluate twenty genotypes of chrysanthemum under naturally ventilated polyhouse during 2019–21. The experiments were laid out in CRD with three replications for growth and flowering traits to determine the variability, heritability, genotypic and phenotypic coefficient of variation, correlation and path coefficient among 9 quantitative traits. Results revealed that magnitude of the genotypic coefficient of variation (GCV) was higher than phenotypic coefficient of variation (PCV) for all the traits. High (>20%) PCV and GCV was recorded for number of flowers per plant, plant height, number of branches plant-1, number of leaves plant-1, flower diameter and days to bud initiation. Heritability estimates ranged from 82% (number of branches plant-1) to 99% (plant height). High heritability coupled with high genetic gain as per cent of mean was recorded for all the traits studied. The number of flowers per plant exhibited positive and significant correlation with number of branches plant-1, number of leaves plant-1, days to bud initiation and days to optimum flowering. Path coefficient analysis using correlation coefficients revealed that days to optimum flowering, plant height and days to bud initiation contributed highest positive direct effect on number of flowers plant-1. Therefore, the selection on the basis of traits viz., number of branches plant-1, number of leaves plant-1, days to bud initiation and days to optimum flowering will be more effective for improvement of traits in breeding of chrysanthemum.